The Impact Of Application Of Value Clarification Technique (VCT) Towards Ecoliteracy And Critical Thinking Skill Student Of Social Science In Primary School - Dadang Iskandar; Deasy Rahmawati; Acep Roni Hamdani (STAI Miftahul Ula Nganjuk, 2019)
The purpose of this study was to determine the effect of the application of Value Clarification Technique (VCT) to ecoliteracy and critical thinking skills of elementary school students in learning Social Science. The method used in this study is a quasi experimental design with non-equivalent control group design, using the two study groups. Subjects in this study were students of class IVSDN Cijerah Indah, Bandung Kulon District Bandung City. The experimental group was given the treatment of learning Value Clarification Technique (VCT) and the control group was given conventional learning. The results showed that in general there is a difference between learners ecoliteracy experimental class and control class and critical thinking skills among learners experimental class and control class after each class has been getting treatment that has been set.